Dampak Inovasi Pemerintahan Terhadap Restrukturisasi Kelembagaan Pemerintahan Di Kota Bandung - Johannes, Ayu Widowati; Sarihati , Tati (Institut Pemerintahan Dalam Negeri, 2025)
Government innovation has become a crucial strategy in responding to the pressures of globalization, rapid digitalization, and rising public expectations for more efficient, transparent, and accountable public services. This study aims to examine how government innovation influences institutional restructuring in Bandung City and its consequences for local governance. Using descriptive qualitative methods, data were collected through document analysis, observation, and in-depth interviews with 16 key informants, including government officials, civil servants, members of the Regional Representative Council (DPRD), and community representatives. Findings indicate that various digital innovations, such as the Sadayana, HAYU, Gampil, and SiBISA applications, as well as the development of the Public Service Mall (MPP), not only improve the quality of public services but also trigger structural and cultural shifts within the bureaucracy. Institutional changes are evident in the establishment of the Regional Development Planning, Research, and Innovation Agency as an innovation center, the repositioning of the Regional Apparatus Organization with the Communication and Information Agency as its digital backbone, and the strengthening of human resource capacity through digital literacy programs. Innovation also strengthens the principles of good governance, particularly transparency and public participation, through mechanisms such as e-budgeting, e-planning, and digital complaint channels. A distinctive contribution of this research lies in highlighting the reciprocal relationship between innovation and institutional restructuring, each serving as a prerequisite and enabler for successful governance transformation. This dynamic points to a paradigm shift from the efficiency-focused New Public Management (NPM) model to digital governance, which prioritizes data integration, cross-sector collaboration, and inclusivity.